Educational characteristics of students with learning disabilities - Galvydytė, Jelena; Ališauskas, Algirdas (Special Education, 2016)
The article describes educational characteristics of students with learning disabilities. The participants of the research (students, parents, teachers, specialists) have been submitted questions about the child’s learning situation and the support provided at school and home. The answer analysis revealed positive and negative factors that affected the students with learning disabilities during the process of teaching and learning. Majority of these environmental factors (the children’s preparation to learn, learning environment, family support and assistance, collaboration of educators) are more construed as favourable rather than unfavourable by participants of the educational process (teachers, special educators, students and their parents). Moreover, the research discloses positive tendencies of education of students with learning disabilities (greater orientation to students’ achievements instead of difficulties; peer support and the like). It is ascertained that poor inclusion and involvement of children and parents as education partners is the issue that remains relevant.